Influence of Annealing Condition on the Structural and Photovoltaic Properties of Cu(In,Ga)(S,Se)₂ Solar Cells - Pham, Anh Tuan; Nguyen, Xuan Quang; Tran, Duc Huy; Dang, Viet Anh Dung; Vu, Ngoc Phan; Nguyen, Duy Cuong (Old Journal, 2017)
Cu(In,Ga)S₂ (CIGS) nanoparticles were synthesized at 250 °C in oleylamine solvent by hot-injection method. Cu(In,Ga)(S,Se)₂ films were fabricated by printing CIGS nanoparticles on molybdenum substrates, then annealed at different temperatures in the range of 500-560 °C under Se vapor ambiance. After annealing, the crystallization of films was significantly improved, the big size CIGSSe crystallites were formed. Only single phase of CIGSSe existed in the films. The best conversion efficiency data of CIGSSe solar cell fabricated at 540 °C shows the best values of parameters. The parameters of the best CIGSSe solar cell are short-circuit current density (Jsc) of 27 mA/cm², open-voltage (Voc) of 0.42 V, fill factor (FF) of 0.36, and conversion efficiency (η) of 4.23%.